1957
DOI: 10.1172/jci103430
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Sodium and Chloride and the Extracellular Fluid Volume in the Rat1

Abstract: Our attempts to gain information concerning the amount of electrolyte in cell water and the theoretical concentration of intracellular cations necessarily revolve around our ability to partition total body water into extracellular and intracellular phases. The total body potassium, for example, is confined almost exclusively to the intracellular phase, and if the intracellular volume of the body could be defined, the net intracellular potassium concentration could be readily calculated as:Total body K -Extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

1959
1959
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…However, no inwith encephalopathy caused by fulminant hepatic failure. 17 Chloride space as determined in the present study 21 has crease in the chloride space was found in the forebrain region, where a significant increase in water content was been used to assess extracellular space in the brain 37,38 and other fluid compartments. 39 The increased hindbrain shown, which would suggest a cytotoxic mechanism.…”
Section: Modified Aftermentioning
confidence: 72%
See 1 more Smart Citation
“…However, no inwith encephalopathy caused by fulminant hepatic failure. 17 Chloride space as determined in the present study 21 has crease in the chloride space was found in the forebrain region, where a significant increase in water content was been used to assess extracellular space in the brain 37,38 and other fluid compartments. 39 The increased hindbrain shown, which would suggest a cytotoxic mechanism.…”
Section: Modified Aftermentioning
confidence: 72%
“…Chloride space was measurement of blood glucose concentrations. Glucose concentracalculated using the method of Cheek et al 21,22 tions were determined by an enzymatic method 18 …”
mentioning
confidence: 99%
“…A final 10 % correction for estimated intracellular bromide (0.90) was used as suggested by the data from CHEEK et al [8][9][10][11]. Loss of bromide in the urine was assumed to be negligible on the basis of stable bromide concentrations in serum from 3 to 15 h after injection as observed by FINK and CHEEK [21] and confirmed in this laboratory.…”
Section: Methodsmentioning
confidence: 93%
“…Edelmann and Leibman (43) subsequently considered the value of 12% for the human adult. Cheek et al (24) found in the rat that some 30% of Na was outside the ECF. The correction of the Naf space for nonextracellular Na+ and the C1-space for intracellular C1-in separate experiments yielded ECVs that were almost identical.…”
Section: Is Ecv Of Brain a One-or Two-compartment System?mentioning
confidence: 99%